(3GdHOQ GdWGdY HeMGSf ef HYO GdbQf GdSGHYs - (3GdThcGfj, eMeO Hf Ydj Hf eMeO Hf YHO Gddg (B, (3J (B1250 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdfXQ aj CNHGQ ef ZHQ CYXe GdYHQ aEfg deG TGY Ydi CdSf LeGYI ef GdQYGY GNJUGU Sda gPg GdCeI HEMQGR aVjdI GdSHb aj GdYdhe Ohf NdagG MJi GTJgQ Yf LeGYI s
(3BNQgG (B:s
(3jhSa BZG GdQhej CMO NhGU GdHGTG Ndjd GdhGUd dMQH GdCTQGa GdeSJhdj Ydi GdeedcI GdJi cGfJ HjO GdTQja MehO hhdOg GMeO hgj GdHdGO GdYQjTjI heG CNPg MehO ef GdHdGO GdEeGejI HEYGfI CUMGH GdfLOj dg hPdc GddMjI hGdMOjOI hRHjOhLQJ gfGc MQhH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\298s
(3EjVGM Gdecfhf (B1\171s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs